The influence of zeranol on certain blood biochemical values of male lambs - Ahmet ACET; Muhtar TİFTİK; Bünyamin TRAŞ; Nuri BAŞPINAR (Eurasian Journal of Veterinary Sciences)
The concentrations of glucose, total protein, Na+, K+, glutamic oxalacetic transaminase (GOT) and Cholesterol in blood serum were determined to investigate certain biochemical aspects of the mode of action of zeranol. Experimental animals (male lambs of Konya merinos) consisted of control (Ili5 untreated), Group I (15 male lambs implanted with 112 mg Zeranol) and Group II 015 male lambs implanted with twice H2 mg Zeranol at fourty fivedays intervals). Blood samples were taken at intervals of 15 days and concentrations of glucose, total protein, Na+, K+, GOT and cholesterol in blood serum were determined. The effects of Zeranol on blood biochemical values were found to be significant, except for Na+ and K+ values. Concentrations of glucose in Group I and Group II were higher than in Control. This increase was significant (P < 0.01). The differences among group were found statistically to be important (P < 0.05, P < 0.01) at 0.15. and 45. days. The levels of cholesterol botih Control and Group I and Group II were high. Acording to statistics analysis, the variation of concentrations within groups were important in Group I and Group II (P < 0.05). However, the differences among groups were shown to be significant at 45. days (P < 0.01). At the begining, concentrations of total protein in Control, Group I and Group II were respectively 6,06 ± 0,09, 6,01 ± 0,16 and 5,96 ± 0,02 gr/dl. At the end of trial, these values were decreased to 5,89 ± 0,14, 5,66 ± 0,23 and 5,67 ± 0,16 respectively. The decreases of concentrations of tota] protein in Control; Group I and Group II were found to be significant as statistics (P<0.01). Concentrations of glutamic oxaloacetic transaminase (GOT) were higher (P < 0.01). in implanted than in Control males. It was shown to decreas the K+ values, in increasing the concentrations of Na+ in all groups. The increase and decrease of the values of Na+ and K+ were significant statistically (P<0,01). However, the values of Na+ and K+ among groups Were only found to be differences at 60. and 120. days (P < 0.05, P < 0,01) and 120. days (P < 0,05) respectively.